2017
DOI: 10.3346/jkms.2017.32.7.1187
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mortality in Severely Injured Patients Using Hospital-based Helicopter Emergency Medical Services in Interhospital Transport

Abstract: Recent evidence has demonstrated the survival benefits of helicopter transport for trauma patients. The purpose of this study was to evaluate the effectiveness of hospital-based helicopter emergency medical services (H-HEMS) in comparison with ground ambulance transport in improving mortality outcomes in patients with major trauma. Study participants were divided into 2 groups according to type of transport to the trauma center; that is, either via ground emergency medical services (GEMS) or via H-HEMS. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…Previous reports also demonstrated the beneficial impact of EAMT on mortality in severe blunt trauma [ 2 ] and seriously injured patient. [ 3 , 4 , 21 , 22 ] The utilization of EAMT for patients with serious traumatic injuries may be expensive, but it is justified by its cost-effectiveness [ 23 ] and the low in-hospital mortality observed in our study. Our study also concurred with the Japanese study by Ohara et al on the safety and usefulness of emergency maternal transport using helicopter.…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports also demonstrated the beneficial impact of EAMT on mortality in severe blunt trauma [ 2 ] and seriously injured patient. [ 3 , 4 , 21 , 22 ] The utilization of EAMT for patients with serious traumatic injuries may be expensive, but it is justified by its cost-effectiveness [ 23 ] and the low in-hospital mortality observed in our study. Our study also concurred with the Japanese study by Ohara et al on the safety and usefulness of emergency maternal transport using helicopter.…”
Section: Discussionmentioning
confidence: 95%
“…For example, some individuals in South Korea cannot have their medical care needs met, due to the lack of geographical accessibility of medical services, although most public healthcare services have been held accountable by the Korean government for a long time [2]. Recent studies found that the probability of mortality after an emergency was affected by the distance from an emergency hospital [3,4]. Social inequity in public health has been a challenging issue in social and community welfare, and many researchers have examined the geographical aspects of such an issue [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…affected by mountains, water), the probability that HEMS may be faster is high. Regarding this issue, some have proposed using distances between hospitals or the expected duration of transfer to justify the use of HEMS [ 15 , 16 ], but there is no consensus on a cut-off distance or time for which the helicopter should be used [ 5 ]. Kristiansen et al showed an increase in the use of HEMS proportional to the distance to be covered, and a decrease in mortality for transfers by HEMS ≥100 km [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kristiansen et al showed an increase in the use of HEMS proportional to the distance to be covered, and a decrease in mortality for transfers by HEMS ≥100 km [ 15 ]. Another study recommends considering HEMS for distances ≥30 km by road for IFT [ 16 ]. If we transpose these values to our study, we note that 738 (75%) missions were above the 30 km proposed limit, and 70 (7%) above the 100 km limit.…”
Section: Discussionmentioning
confidence: 99%